Some construction parameters of unglazed perforated solar dryers for medicinal plants - Hassanain, Ahmed A. (International Journal of Agricultural and Biological Engineering, 2010)
Abstract: Erecting solar dryers for medicinal plants require the best design option to suit such plants. Investigations were carried out on some design parameters of the unglazed perforated solar dryers under the prevailing weather conditions of Ismailia, Egypt. Effects of different parameters on the heat exchange effectiveness were investigated. Parameters considered in this study including hole (perforation) diameters, dimensions apart, material being used and its thickness all were investigated to reveal the effects of suitable suction velocity, prevailing wind speed and its direction under the simulated incident solar radiation of the investigation site. Based on the obtained results for heat exchange effectiveness under controllable conditions, solar drier was built and investigated outdoors under the prevailing weather conditions of the investigation site. Holes diameter of 3 mm for all the investigated plates and under the different conditions resulted the highest obtained heat exchange effectiveness. Diamond shape for Holes distribution with dimensions of 29 mm×29 mm apart gave higher heat exchange effectiveness above the commonly used distribution (square shape). Temperature increase above ambient per unit of incident radiation was found as (0.0162±0.0007)<span style="line-height: 140%; font-family: